An Improved Load Spectrum Extrapolation Method of Railway Vehicle Bogie Frame. Issue 2 (March 2021) - Ma, Shuang; Sun, Shouguang; Wang, Binjie; Wang, Ning
Abstract: This article is aimed to seek for a precise extrapolation method on railway vehicle bogie frame load spectrum based on real engineering problem in China Standard EMU and Beijing Subway vehicle. The most common used methods, exceeding probability and standard load spectrum with cumulative frequency, are discussed. An improved method that excludes trivial load amplitude while calculating cumulative frequency is proposed. The three methods are deployed with real measured data and then compared with the ground truth. The comparison result shows that the improved method introduced in this article has the minimum error of the estimated load maxima and least deviation from ground truth load spectrum.